Dampak Implementasi E-Filing dan E-Billing Terhadap Kepatuhan Wajib Pajak - Fitria Novi Nuraini (Akuntansi, 2024)
Taxes are one of Indonesia's main sources of income. In the government's efforts to improve tax compliance, e-filing and e-billing systems are used. The aim of this research is to find out how the implementation of e-filing, e-billing systems and better understanding of taxes affects taxpayer compliance in the city of Bandung. This research uses quantitative methodology. The research population is taxpayers registered at KPP Pratama Bandung Cibeunying. The research sample was 100 individual taxpayer respondents registered at KPP Pratama Bandung Cibeunying. The research hypothesis was tested using multiple regression analysis. Research shows that the use of e-filing and e-billing does not partially influence the increase in taxpayer compliance in Bandung City, and understanding tax levels only slightly influences this increase. Research shows